Pemanfaatan Platform Merdeka Mengajar dalam Praktik Baik Implementasi Kurikulum Merdeka - Thoriq, Alfan; Hidayati, Dian; Rina (Universitas Kristen Satya Wacana, 2024)
The lack of teacher involvement in independent training and the absence of references to good practices in implementing this curriculum pose significant obstacles. To address this, an educational platform known as the Merdeka Belajar Platform was developed, aimed at facilitating teachers' access to inspiration and references. This research examines the utilization of the Merdeka Belajar Platform in implementing the independent curriculum effectively, focusing on SMAS Muhammadiyah Toboali as a case study. The study's purpose is to uncover and analyze the use of the Merdeka Belajar Platform in facilitating effective implementation of the independent curriculum at SMAS Muhammadiyah Toboali. Descriptive qualitative research methods were employed, involving interviews, documentation studies, and observation for data collection. The findings revealed initial difficulties in comprehending the independent curriculum due to the rapid transition process. However, the implementation of the Merdeka Belajar Platform has led to positive changes, with the optimization of the school's learning community and the emergence of good practices among colleagues. This mutual support system among teachers has underscored those advancements in science and technology present opportunities and challenges rather than obstacles, thereby enhancing educators' capacity and capabilities.